Book review: Mirumachi, Naho. 2015: Transboundary Water Politics in the Developing World. (April 2017) - Chokkakula, Srinivas
Mirumachi, Naho. 2015: Transboundary Water Politics in the Developing World . Oxon: Routledge. 190 pp. £85.00 (Hardcover). ISBN: 9780415812955.